Anti-Fungal Activity Testing of Purple Cabbage (Brassica oleracea Linn.) Ethanol Extract in Inhibiting The Fungi Growth Candida albicans and Malassezia furfur - Khairani, Tetty Noverita; Fitri, Khairani; Andry, Muhammad; Sarumaha, Paska Eli (Jurnal Biologi Tropis, 2024)
One of the plants that has the potential to be utilized as medicine is purple cabbage (Brassica oleracea Linn.). Commensal fungi like Candida albicans and Malassezia furfur can be found in the genitourinary tract, vagina, urethra, skin, fingers, and toes, among other places on the body. The purpose of: The study aimed to learn more about the antifungal properties of the ethanol extract of purple cabbage in preventing the growth of Malassezia furfur and Candida albicans. This study used an experimental design to examine the independent variables of the purple cabbage extract with various doses of the growth activity test of Candida albicans and Malassezia furfur, as well as their inhibition zones. Purple cabbage contains steroids, saponins, tannins, and flavonoid compounds. With concentrations of 10%, 20%, 30%, and positive control, the average diameter of the inhibitory zone for Candida albicans was 4.83 mm, 7.2mm, 8.75mm, and 6.21mm. The concentrations of Malassezia furfur at 10%, 20%, 30%, and the positive control were 4.61mm, 6.36mm, 8.83mm, and 6.15mm, respectively. As a negative control, DMSO failed to exhibit an inhibitory zone. Statistics revealed a substantial difference, indicating that the concentration had an impact on how the inhibition zone developed. The ethanol extract of purple cabbage has antifungal action, and the treatment with the 30% extract concentration forms the optimal concentration. It is advised that more research be done on the antifungal activity of purple cabbage extract against various kinds of fungus and that dosage forms be created for it.